Outcomes of Bridge Plating Versus Standard Fixation in Geriatric Ankle Fractures. Issue 4 (16th October 2019) - Holzgrefe, Russell E; Erwood, Amalie; Maidman, Samuel; Runge, William; Gottschalk, Michael; Bariteau, Jason
Category: Ankle, Trauma Introduction/Purpose: Ankle fractures represent one of the most common injuries encountered by foot and ankle specialists. Internal fixation of the lateral malleolus can be achieved by several different techniques, most commonly by lag screw and neutralization plating. However, ankle fractures in older patients often present technical challenges as osteoporotic bone is more commonly encountered which may require bridge plating techniques. This study compares outcomes in patients over age 50 years who underwent ORIF of the lateral malleolus with either a bridge plate or lag screw and neutralization plate technique. Methods: This retrospective study evaluated 56 patients with closed ankle fractures, aged over 50 years who underwent open reduction internal fixation of the lateral malleolus. These were divided into two groups: 36 patients had fixation with one or more lag screws and a neutralization plate, and 20 patients had fixation with a bridge plate technique. Fractures were stabilized with lag screw fixation when feasible, while bridge plating was utilized in patients where lag screw fixation was not possible. SF-36 scores were attained at a minimum one-year post-op. Final radiographs and complications were recorded. Results: The lag group had a mean age of 63 years, 17% men, 61% with syndesmotic screw fixation, and 56% with medial malleolus fixation. The bridge group had a mean age of 65 years, 15% men, 60% with syndesmotic screw fixation, and 70% with medial malleolus fixation. At minimum one-year, SF-36 physical component summary score was 74.2 ± 19.4 in the lag group vs 63.2 ± 24.8 in the bridge plate group (p=0.049). The SF-36 mental component summary score was 89.2 ± 12 in the lag group vs 75.5 ± 22.7 in the bridge plate group (p=0.009). One patient in each group required return to the OR for irrigation and debridement for infection. No patients experienced fixation failure and all fractures demonstrated union on final radiograph. Conclusion: In the present study of patients over age 50 years who underwent ORIF of an ankle fracture, as compared with bridge plating, lag screw and neutralization plating is associated with superior one-year SF-36 physical and mental summary scores with similar rates of complications. However, additional research is needed to determine to what degree this difference is causative or correlative with confounding variables as fixation technique was not found to be an independent predictor of SF-36 outcomes in this small cohort.